PERAN SERIKAT PEKERJA DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Yuhari Robingu (Perspektif, 2005)
Right to unite freely gather and expel opinion is a human rights. This right in Indonesia has receive law guarantee as has been stated in article 28 e paragraph (3) UUD 1945 which stated that “Every person has a right to unite, gather and expel opinion freely. "Worker is the part of Indonesian citizen, therefore they have right to be protected One kind of law protection that given by government for every worker is guarantee to unite and gather freely in an organization that called Union. The existence of Union today is more guaranteed with the existence of law No. 21 year 2000 about Union. Union is a media to create harmonic, dynamic, and justice in Industrial Relation that suitable with the valid law. If there is any dispute about Industrial Relation, Union is one of the parties in industrial relation dispute settlement.